Dipole magnet of synchrotron source for National Synchrotron Centre of Ukraine - Gladkikh, P.I.; Karnaukhov, I.M.; Mytsykov, A.O.; Muratov, V.I.; Peev, F.A. (Вопросы атомной науки и техники, 2001)
The paper contains the revised design of a dipole magnet for a synchrotron radiation source. Usage of such a magnet allows to reach the energy of electrons in a ring up to 1.2 GeV. In paper the result of simulation of a magnet for all modes of operations of a source are shown. The proposed variant of the dipole magnet considerably raises parameters of the synchrotron radiation source.